Masa Depan Akuntansi: Akankah AI Menggantikan Akuntan - Rina Amelia; Benardi Benardi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The development of digital technology, particularly Artificial Intelligence (AI), has brought significant changes to various industrial sectors, including accounting. In recent years, AI has become an essential tool used in various business applications, such as data processing, predictive analysis, and automated financial reporting. This technology can automate routine tasks like data entry and account reconciliation, which previously required human intervention, thereby increasing efficiency and reducing potential human errors. However, the application of AI in accounting has sparked discussions about the future of this profession. While AI can automate many aspects of accounting, it cannot fully replace human accountants, especially in areas requiring data interpretation, strategic decision-making, and ethical considerations. The webinar conducted for this study explored the implications of AI in accounting, highlighting both the opportunities and challenges of integrating AI into accounting practices. The findings emphasize the importance of adaptive accounting education and the need for continuous professional development to prepare future accountants to work in an increasingly digital and automated environment. Therefore, the future of the accounting profession will be determined by how AI and human accountants can work together to achieve the best outcomes, maintaining high ethical and professional standards.